The Problems of Meniscal Root Tears - Zazirnyi, I.M.; Kostrub, O.O.; Smigielski, R.; Andreev, A. (TERRA ORTHOPAEDICA, 2020)
Meniscal root tears are defined as radial tears located within 1 cm from the meniscal attachment or a bony root avulsion. This injury is biomechanically comparable to a total meniscectomy, leading to compromised hoop stresses resulting in decreased tibiofemoral contact area and increased contact pressures in the involved compartment. These changes are detrimental to the articular cartilage and ultimately lead to the development of early osteoarthritis. Surgical repair is the treatment of choice in patients without significant osteoarthritis (Outerbridge grades 3 or 4). Root repairs have been reported to improve clinical outcomes, decrease meniscal extrusion and slow the onset of degenerative changes. In this article, we describe the anatomy, biomechanics, clinical evaluation, treatment methods, outcomes, and post-operative rehabilitation for posterior meniscal root tears.